Pengaruh Work Life Balance Dan Kompetensi Terhadap Kinerja Pegawai Pada Dinas Perhubungan Kota Tasikmalaya - Hagi Akbar Alamsyah; Depy Muhamad Pauzy; Dudu Risana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research purposse to determine and analyze the influence of work life balance and competence, both simultaneously and partially, on employee performance at the Tasikmalaya City Transportation Service. The method used in this research is a survey with a descriptive approach. With a research sample of 99 State Civil Apparatus as respondents. The data used is primary data. The analytical tool used in this research is multiple linear regression using the SPSS version 25 support application. The test results show simultaneously there is a significant influence of Work Life Balance and Competence on Employee Performance and that partially the variables used in the research, namely work life balance and competency, have a significant effect on the performance of employees at the Tasikmalaya City Transportation Service.